Theoretical Study to Fatigue Crack Growth to Duplex Steel Alloy byGeneralized Paris Equation - Khadum, H. N.; Hussain, F. I.; Salih, M. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
A theoretical study was done in this work for Fatigue , Fatigue Crack Growth (FCG) and stress factor intensity range for steel .       It also includes Generalized Paris Equation and the fulfillment of his equation which promises that there is a relation between parameters C and n .          Usig Simple Paris Equation through which we concluded the practical values of C and n and compared them with the theoretical values which have been concluded by Generalized Paris Equation .           The value of da/dN and âˆ†K for every material and sample were concluded and compared with the data which was used in the computer program for the whole of our research .            The program is written in Fortran . The theoretical and practical data was drawn with (Graf) program so as to conclude the data  mentioned in the research .